2016
DOI: 10.4049/jimmunol.1502676
|View full text |Cite
|
Sign up to set email alerts
|

Blomia tropicalis–Specific TCR Transgenic Th2 Cells Induce Inducible BALT and Severe Asthma in Mice by an IL-4/IL-13–Dependent Mechanism

Abstract: Previous studies have highlighted the importance of lung-draining lymph nodes in the respiratory allergic immune response, whereas the lung parenchymal immune system has been largely neglected. We describe a new in vivo model of respiratory sensitization to Blomia tropicalis, the principal asthma allergen in the tropics, in which the immune response is focused on the lung parenchyma by transfer of Th2 cells from a novel TCR transgenic mouse, specific for the major B. tropicalis allergen Blo t 5, that targets t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In a recent report, transfer of T H 2 cells and lung stimulation with Blomia mite protein allergen caused severe lung inflammation, through increased type-2 inflammation (IL-4 and IL-13). 48 In this model, increased mucus hypersecretion, tissue remodelling and severe inflammation were observed. 48 Most models use repeated chronic allergen challenges to induce tissue remodelling, which are characterized by allergen-specific T H 2 responses.…”
Section: Chronic Inflammation and Tissue Remodellingmentioning
confidence: 80%
See 1 more Smart Citation
“…In a recent report, transfer of T H 2 cells and lung stimulation with Blomia mite protein allergen caused severe lung inflammation, through increased type-2 inflammation (IL-4 and IL-13). 48 In this model, increased mucus hypersecretion, tissue remodelling and severe inflammation were observed. 48 Most models use repeated chronic allergen challenges to induce tissue remodelling, which are characterized by allergen-specific T H 2 responses.…”
Section: Chronic Inflammation and Tissue Remodellingmentioning
confidence: 80%
“…48 In this model, increased mucus hypersecretion, tissue remodelling and severe inflammation were observed. 48 Most models use repeated chronic allergen challenges to induce tissue remodelling, which are characterized by allergen-specific T H 2 responses. Chronic asthma models typically consist of an initial allergic sensitization step, followed by repeated low-level allergen exposure/challenge over an extended period of time (up to 12 weeks) to induce chronic allergic inflammation.…”
Section: Chronic Inflammation and Tissue Remodellingmentioning
confidence: 80%
“…Recent studies have shown that IL-33 cytokine is the key element that links early events after lung epithelial cells contact with the allergen and Th2 response, resulting on asthma [9] , [44] . An experimental mice model receiving CD4+ effector Th2 cells, exposed to Bt antigens have developed lung eosinophilia, hyperplasia of smooth muscle cells and goblet cell, as well as overproduction of IgE and mucus production through IL-13 [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a disease that affect the life of people, being more prevalent in childhood [1] . Blomia tropicalis (Bt) mite rapidly settles in homes of climates countries such as Brazil [2] , being the main asthma-induced allergen in the tropics [3] , [4] , [5] , [6] . Atopic asthma is characterized by inflammation of airways, with predominance of Th2-type cytokines, as IL-13, and eosinophilic inflammation [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In asthma, the imbalance of the proportion of T-helper type 1 (Th1) to Th2 cells activates the CD4 + Th2 cell immune response and the release of interleukin (IL)-13, −25, −5, −4 and −33, prompting the transformation of B cells into immunoglobulin (Ig)E-secreting cells ( 23 , 24 ). Among these ILs, IL-25 and −33 are known as vital pro-inflammatory mediators that induce the release of Th2-associated cytokines, including IL-5, IL-4 and IL-13, which elevate serum IgE, as well as airway hyperresponsiveness, remodeling and mucus hypersecretion ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%